2018
DOI: 10.2147/dmso.s166728
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic activity and constituents analysis of blueberry (<em>Vaccinium corymbosum</em>) fruit extracts

Abstract: BackgroundTo investigate hypoglycemic activity and elucidate the active composition of the fruit blueberry (Vaccinium corymbosum).MethodsMethanol extracts of blueberry (MEB) were separated using a D101 macroporous resin column to yield quinic acid derivative (Fr.1)- and flavonoid (Fr.2)-rich fractions. The effects of the blueberry extracts on mRNA expression of GLUT-2 (glucose transporter type 2) and PPARγ (peroxisome proliferator-activated receptor-γ), as well as on the activities of PPRE (peroxisome prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Contrarily, the anti-inflammatory effect was less pronounced in some animal studies and human [21, 36, 37]. New reports indicated that blueberry extracts can significantly inhibit inflammatory and apoptosis via activation of JAK1/STAT3 signaling [38], PPARγ activity [39] or survival PI3K/Akt and MAPK/ERK pathways [40].…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, the anti-inflammatory effect was less pronounced in some animal studies and human [21, 36, 37]. New reports indicated that blueberry extracts can significantly inhibit inflammatory and apoptosis via activation of JAK1/STAT3 signaling [38], PPARγ activity [39] or survival PI3K/Akt and MAPK/ERK pathways [40].…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanin-enriched diets increased hypoglycemic activity (51%) compared with phenolic-enriched diets (33%) and metformin-treated controls (32%), suggesting that anthocyanins modulated hyperglycemic and hyperlipidemic activities [ 13 ]. The supplementation of BlBE increased the beneficial glucose metabolism involved peroxisome proliferator response element (PPRE) (1.3–1.8%), glucose transporter 2 (GLUT-2) (1.5%), and PPAR-γ (1.4%) activities, and reduced the proinflammatory nuclear factor (NF)-κB activity [ 14 ]. Furthermore, an increase in the intercellular levels of the mRNA of glucose transporter (GLUT4), insulin receptor substrate-1/2 (IRS-1/IRS-2) (insulin response mediators regarding glucose metabolism), and AMP-activated protein kinase (AMPK) (a key regulator of mitochondrial biogenesis and cellular energy homeostasis) were observed in skeletal muscles, indicating increased glucose uptake [ 15 , 16 ].…”
Section: Blueberriesmentioning
confidence: 99%
“…Blueberry polyphenols prevent heart diseases, which are associated with the reduction of calpain activity and oxidative stress [ 54 ]. Blueberry extract has hypoglycemic activity exerted by promoting the expression of GLUT-2 and PPARγ and controlling the inflammatory pathway; based on interaction between caffeoylquinic acid derivatives and quercetin glycosides [ 132 ]. Blueberry polyphenols and its fermented beverages can inhibit α-amylase and α-glucosidase of starch-degrading for type 2 diabetes management [ 133 ], however polyphenols can regulate the immune function which exists as a mediator role of epigenetic mechanisms [ 134 ].…”
Section: Major Mechanisms and Structural Activity Of Blueberry Commentioning
confidence: 99%